Menyusui Setelah Kembali Bekerja: Sistematik Review - Siti Nurjanah; Riadini Wahyu Utami (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
ABSTRACT The work of the mother is cited as a major potential obstacle in exclusive breastfeeding and is a factor that can reduce the duration of breastfeeding. The time the mother returns to work has an impact on the duration of breastfeeding. This study used systematic review where a systematic review was conducted following a combination of preferred reporting items for systematic review and meta-analysis (PRISMA). The database uses ScienceDirect, SpringerLink, CINAHL, ProQuest, SAGE journals, and PubMed). Based on the results of the article search, 15 selected articles related to breastfeeding mothers returning to work were obtained. The prevalence of exclusive breastfeeding was 75.7%. Have a short period of maternity leave (AOR 9.3; 95%CI 3.8, 23), be a full-time employee (AOR 3.5;95% CI 1,7,11), be a private employee (AOR 2.1), less flexible working time (AOR 3.0 95% CI 1.2) do not pump breast milk (AOR 4.3 95%CI 1.7, 11), lack of breastfeeding rest rest (AOR 6.7;95% CI 3,14,5) and a workplace away from her child (AOR 3.1;95% CI 3.1, 6.3) significantly associated with the cessation of EBF among working mother. The conclusion of this research is That maintaining breastfeeding requires time and commitment from the mother, as well as a supportive workplace or learning environment. Keywords: breastfeeding, work, systematic review